Organizational empowerment among Nursing Faculty in the Northwestern Region of Saudi Arabia - Alsaqri, Salman Hamdan; Pasay-an, Eddieson; Villacorte, Liza; Madjid, Fredezwinda; Pacis, Carmencita; Al-Sadi, Ahmad Khalil Ahmad (Makara Journal of Health Research, 2020)
Background: This study aimed to determine the differences in the workplace empowerment of nursing faculty as it relates to their demographic information. Methods: A comparative cross-sectional study was conducted among 65 nurse educators at the College of Nursing, University of Hail, Saudi Arabia. The data were collected through a survey questionnaire between January and March 2019. Results: Significant differences were found regarding gender and opportunity (p < 0.017), support (p < 0.020), resources (p < 0.022), job activities scale (JAS; p < 0.005), organizational relationship scale (ORS; p < 0.011), and marital status on resources (p < 0.031). In comparison, gender to information and all of the other demographic variables such as marital status (except resources), years of experience, age, nationality, educational qualifications, and specialization were found insignificant to opportunity, support, resources, information, JAS, and ORS, where all of their p-values were more than 0.05. Conclusion: Male nursing faculty were found to be more empowered in terms of opportunity, support, resources, JAS, and ORS but not to information. Married nursing faculty were found more empowered only to resources. This study supports that gender and information, marital status (except resources), years of experience, age, nationality, educational qualifications, and specialization are not determinants for job empowerment.